Learning of Santri with the Community in Empowering Entrepreneurship at the Al-Amin People's Islamic Boarding School, Sumberpucung, Malang Regency - Ahmad Thohari; Muhammad Khoirul Fatihin; Lasi Purwito; Zulkarnain; Hardika; Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study explores the collaborative learning process between santri and the local community in entrepreneurship empowerment at Al-Amin People's Islamic Boarding School, Sumberpucung, Malang, while analyzing the pesantren's role in facilitating that process. Islamic boarding schools do not function solely as religious-based educational institutions; they can also be regarded as institutions that nurture generations with Islamic character while simultaneously serving as social institutions for community empowerment. This study employs a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation study, and were analyzed using the interactive model. Credibility of findings was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that the collaborative learning process between santri and the community unfolds in a gradual and staged manner, with the overarching goal of empowering the surrounding community. Realizing this shared learning process requires the active role of the pesantren under the leadership of its caretaker, encompassing three complementary dimensions: first, the Islamic boarding school as facilitator, providing skills training, business facilities, and mentoring; second, as initiator of entrepreneurship empowerment programs responding to low economic development in Sumberpucung; and third, as a driving agent through integrated social and economic activities engaging all elements of the surrounding community. The findings are expected to enrich scholarly discourse on community and santri empowerment within Non-Formal Education, offering an empirically grounded model that highlights the interplay between cultural authority, participatory mobilization, and community autonomy development.